MYCOTOXIN CONTAMINATION ON CORN USED BY FEED MILLS IN INDONESIA - Budi Tangendjaja; Sri Rachmawati; Elizabeth Wina (Indonesian Agency for Agricultural Research and Development, 2008)
Mycotoxins which are secondary metabolites of fungi contaminate agricultural products such as corn and have deleterious effects on human and animal. The objective of this study was to evaluate the mycotoxin contamination on local and imported corn samples collected from different feed mills in Indonesia. Three hundred fifty six of corn samples (0.50 kg each) were sent by several feed mills to the Indonesian Research Institute for Animal Production during 2005-2006. The background information accompanied with each sample was country/province of origins, harvesting seasons, postharvest drying methods, moisture levels, grades, and varieties. The samples were analyzed for various mycotoxins, i.e aflatoxin (AFL), ochratoxin (OCRA), zearalenone (ZEN), fumonisin (FUM), deoxynivalenol (DON), and T2 toxin using commercial kits, except for AFL which was analysed using a kit developed by the Indonesian Research Center for Veterinary Science. The results showed that average AFL level in the contaminated corn originated from Indonesia was 59 µg kg-1, almost 7 times higher than that imported from the USA or Argentina. Among the types of mycotoxins detected, FUM was the highest with an average of 1193 µg kg-1, followed by DON, ZEN and OCRA at level of 324, 22 and 2 µg kg-1, respectively. Mycotoxin levels in the contaminated local corn samples varied depending on the province of origins as well as harvesting seasons, postharvest drying methods, and moisture contents. The least mycotoxin contaminations were found on corn originated from NorthSumatra and Lampung with the AFL levels were < 20 and < 50 µg kg-1, respectively, lower than those from East Java, Central Java and South Sulawesi (64-87 µg kg-1). Mycotoxin levels, however, were less affected by grading made by feed mills and corn varieties. It is indicated that AFL was the most important mycotoxin as far as for animal feeding concerned, as it contaminated almost 50% of local corn with the level of contamination above the Indonesian National Standard, i.e. 50 µg kg-1. The study suggests that postharvest methods of local corn must be improved to reduce mycotoxin contamination.